ORGANISATIONAL JUSTICE AND ORGANISATION COMMITMENT IN SELECTED GOVERNMENT-OWNED PARASTATALS IN RIVERS STATE, NIGERIA - B. M. Nwibere (Journals Park Publishing, 2022)
The study examined the relationship between organizational justice and organizational commitment. A total of 450 employees were randomly chosen from 20 purposively selected Federal, State and Local Government-owned agencies in Rivers State, Nigeria. A quasi-experimental design was utilized, and data was collected through a cross-sectional survey as it is the most appropriate for the administrative sciences. The Spearman Rank Correlation Coefficient and the Multiple Regression Model via the Statistical Package for Social Sciences (SPSS) Version 15 were utilized for data analysis. The result of data analysis unveiled a positive but weak and significant association between organizational justice and organizational commitment across the chosen government-owned agencies. Specifically, distributive justice, procedural justice, and interactional justice were identified to exert a positive but weak influence on employees' affective, normative, and continuance commitments respectively in the Federal, State, and Local Government-owned agencies in Rivers State. Consequent to these findings, the study concludes that the execution of distributive justice, procedural justice, and interactional justice in the Federal, State, and Local Government-owned agencies in Rivers State was not satisfactory enough as to elevate employees' affective, normative, and continuance commitments to the organization. The theoretical and managerial implications of these findings were also discussed.
Keywords: Affective Commitment, Continuance Commitment, Distributive Justice, Government-Owned agencies, Interactional Justice, Nigeria, Normative Commitment, Organisational Justice, Organisational Commitment, Organisational Performance, Procedural Justice, Rivers State.